A summated rating scale for measuring city image. (April 2015) - Gilboa, Shaked; Jaffe, Eugene D.; Vianelli, Donata; Pastore, Alberto; Herstein, Ram
Highlights: A new scale was developed for measuring city image among residents and tourist populations. The scale was validated using Exploratory and Confirmatory Factor Analyses. The scale development took place in three different cities: Rome, Trieste and Jerusalem. The findings show that there is a need for different scale for the various stakeholders of the city. Abstract: The literature about cities' marketing is replete with articles on the subject of city branding. Included in this literature are articles dealing with the subject of measuring city image, which is a precursor to the development of a city brand. However, many of the image studies lack validity or generalization. This paper presents a methodology for measuring city image, grounded on the development of a scale for this purpose. Based on convergent and discriminant reliability and validity analyses, factors were identified that comprise a city's image among residents and tourists in three cities: Jerusalem, Rome and Trieste. Four factors identified by residents are Municipal Facilities, Leisure, Security and Public Services. Among tourists five factors were identified: Caring, Tourism and Recreation, Security, Public Services and Leisure and Entertainment. Three corresponding factors were identified in both tourists' and residents' replies. The scale validation process indicated that residents and tourists have similarities and differences in their perception of a city. As such, the current finding suggests that the scales developed in this paper may be used when surveying both groups.